Perceraian Yang Dilakukan Oleh Pasangan Yang Melakukan Perkawinan Beda Agama - Rusgiman Fauzan Ruslan; Barzah Latupono; Mahrita Aprilya Lakburlawal (PATTIMURA Law Study Review, 2023)
ABSTRACT: Law Number 1 of 1974 concerning marriage generally only regulates marriage and divorce for those who are married according to the provisions stipulated in the law. However, marriage and divorce are not always carried out by couples who have the same religion and belief, often marriages and divorces are carried out by those who have different religions and beliefs. The purpose of this paper is to find out and explain whether interfaith marriages and interfaith divorce processes are valid or not. The method used in this paper is a normative juridical approach with a statutory approach, a conceptual approach and a case approach. Results of the research basically, interfaith marriages carried out in any way the marital status is invalid, because basically a marriage can be considered valid if it is carried out according to Article 2 paragraph (1) of Law Number 1 Year 1974 concerning Marriage which explains that "Marriage is valid if it is carried out according to the laws of each religion and belief", but in reality interfaith marriages still occur in Indonesia. Divorce between different religions can be carried out in court, namely in particular it can be done in district courts, the process of interfaith divorces conducted in district courts is generally not much different from divorces carried out by couples in general in district courts.